Comparison of Academic Resilience Between Students in State Senior High Schools and Islamic-Based Senior High Schools Based on Learning Outcome in Ternate City - Fiki Febrian Dwi Prasetya; Liasari Armaijn; Siti Umairah (CV. Media Inti Teknologi, 2025)
Background: Students are expected to complete their academic workload optimally. A common problem in education is low ability. Pressures on students include parental demands for grades and achievement, and the demands of a competitive learning environment.Aims: Islamic schools often emphasize the instillation of religious values, while public schools may focus more on the development of broader academic competencies. The aim is to examine and compare the levels of academic resilience between students from public and Islamic-based high schools.Methods: This study employed a quantitative approach using a Likert scale questionnaire and analyzed the data with a one-way ANOVA test in SPSS. Participants were 35 students from SMA Negeri, 27 from SMA Negeri Aliyah, 33 from SMA Muhammadiyah. Results: The